EXPRESSIONIST ECHOES IN “3 AUTUMN” SONGS BY DAN VOICULESCU - STRUCTURE, STYLE, LANGUAGE - Şerban MARCU (Studia Universitatis Babeş-Bolyai. Musica)
The present study advances for analysis the lieder cycle 3 Autumn songs for soprano, oboe, two clarinets and violin from composer Dan Voiculescu’s youth. The three lieder are based on poems Autumn song and Song by Emil Isac and Autumn by Nicolae Labis. The analysis reveals technical, stylistic, aesthetic and rhetoric elements characteristic for this stage in the creative trajectory of the composer, such as the choice of Symbolist poetry and the use of post-Expressionist language, represented by the intensely chromatized melodic, the preference for dissonance and the feeling of temporal suspension generated by rhythm abounding in suspensions and exceptional rhythmic divisions.